The Role Of Certain Nutrients In Improve Stress Resistance In Plants Under Extreme Weather Conditions - Гладкіх, Є. Ю.; Круподеря, Ю. О.; Панасенко, Є. В. (Man and Environment. Issues of Neoecology, 1970)
Purpose.  Determining the role of certain nutrients to minimize the potential negative impacts of extreme weather events and increasing stress tolerance of crops. Methods. Investigations were carried out in conditions of long-term stationary experiment and in a temporary field experiment. Laboratory and analytical studies were carried out using standardized techniques. Results. In extremely dry conditions the balancing nitrogen, phosphorus, potassium and sulfur in fertilizer system and application of microelements during critical periods of growth and development of plants contributes to the improvement in the use of soil moisture and nitrogen and increase crop yields by an average of 20-25%. Conclusions. The adaptation of plants to extreme weather events, such as efficient use of water during droughts, depends on the availability of the necessary nutrients (providing plants with phosphorus, potassium, silicon, sulfur and micronutrients) and their application in the balance for the crop formation at a certain stage of ontogenesis.